Fingerprints of binary black hole formation channels encoded in the mass and spin of merger remnants - Arca Sedda, Manuel (The astrophysical journal, 2020)
Binary black holes (BBHs) are thought to form in different environments, including the galactic field and (globular, nuclear, young, and open) star clusters. Here, we propose a method to estimate the fingerprints of the main BBH formation channels associated with these different environments. We show that the metallicity distribution of galaxies in the local universe along with the relative amount of mergers forming in the field or in star clusters determine the main properties of the BBH population. Our fiducial model predicts that the heaviest merger to date, GW170729, originated from a progenitor that underwent 2-3 merger events in a dense star cluster, possibly a galactic nucleus. The model predicts that at least one merger remnant out of a hundred BBH mergers in the local universe has mass , and one in a thousand can reach a mass as large as . Such massive black holes would bridge the gap between stellar-mass and intermediate-mass black holes. The relative number of low- and high-mass BBHs can help us unravel the fingerprints of different formation channels. Based on the assumptions of our model, we expect that isolated binaries are the main channel of BBH merger formation if of the whole BBH population has remnants with masses , whereas % of remnants having masses points to a significant subpopulation of dynamically formed BBH binaries.